Performance of reinforced lightweight geopolymer composite panels subjected to windborne debris impacts - Li, Zhixing; Chen, Wensu; Hao, Hong (2023)
Lightweight panels have been widely employed as building envelopes in construction. As a result of the rising demand for environmentally friendly building materials, the authors recently developed a lightweight geopolymer composite (LGC) material and investigated the performance of reinforced LGC panels under static loading. Superior performance of LGC panels as compared to conventional panels such as autoclaved aerated concrete (AAC) panels has been observed, demonstrating their potential applications. During strong winds, building envelopes might be subjected to windborne debris impact, which could threaten residents and facilities and lead to structural failure. To explore the application potentials of LGC panels in strong wind regions, in this study, the performances of LGC panels subjected to windborne debris impact were investigated and compared with those of AAC panels by using a pneumatic cannon testing system. The failure modes and damage levels under different impact scenarios of LGC and AAC panels and their impact resistance capacities were obtained, compared and quantified in terms of the projectile residual velocity, penetration length and opening size. The effects of matrix materials, panel thicknesses, impact locations, reinforcement spacings and projectile impact velocities on their impact resistance performance were analyzed. For comparison, the punching shear capacities of the panels were also quasi-statically tested and analyzed subjected to the same projectile employed in the impact tests.